A comparative analysis of China's provincial carbon emission allowances allocation schemes by 2030: A resource misallocation perspective. (10th August 2022) - He, Weijun; Yang, Yuantao; Gu, Wei
Abstract: Carbon emission allowance (CEA) has become a scarce resource against global climate change. Hence, the CEA allocation scheme is critical to improving its utilization efficiency and balancing regional development. However, most of the existing literature mainly focused on the formulation of allocation schemes but ignored the examination of CEA misallocation, which may damage productivity and regional development. This study intends to conduct a comparative analysis of Chinese provincial CEA allocation schemes by 2030 from a perspective of resource misallocation. For this purpose, 15 provincial CEA allocation schemes by 2030 based on the indicator method are developed first. Then a CEA misallocation index deriving from the extended Gini coefficient is proposed to examine the CEA misallocation of proposed schemes. Finally, an empirical analysis of China's provincial CEA allocation by 2030 is conducted. The results indicate that provincial CEA misallocation indeed occurs under the proposed allocation schemes with the CEA misallocation index ranging from 0.209 to 0.311, and the scheme based upon the efficiency principle has a relatively minimum misallocation index at 0.209. Furthermore, CEA misallocation is related to the carbon intensity reduction rate, and the scheme based on the efficiency principle could further achieve optimal CEA allocation when the carbon intensity reduction rate decreases. We suggest relevant decision-makers focus on the efficiency principle when developing a provincial CEA allocation scheme as it has strength in avoiding CEA misallocation. Highlights: Chinese provincial CEA misallocation by 2030 is investigated. The Gini coefficient method is extended to measure CEA misallocation. A comparative analysis of 15 schemes is conducted based upon CEA misallocation. The scheme following efficiency principle can better avoid CEA misallocation. CEA misallocation is closely related to carbon intensity reduction rate.